Physical Therapists Use of Diagnostic Ultrasound Imaging in Clinical Practice: A Review of Case Reports - Robert Manske; Katherine Podoll; Alycia Markowski; Maureen Watkins; Lorna Hayward; Murray Maitland (International Journal of Sports Physical Therapy)
# Objective